Is a Single Rinse Effective on Evacuating the Residual Monomers After Orthodontic Bonding? An In Vivo Study - YILMAZ, BERZA; Gorukmez, Erhan; YILMAZ, BERZA; Ramoglu, Sabri Ilhan (My University, 2021)
Objective: Orthodontic adhesives are known to release potentially harmful bio-chemicals such as Bisphenol A, a derivative from Bisphenol-A-Glycidyl-Methacrylate (Bis-GMA). The aim of this study was to evaluate the amount of Bis-GMA released after the use of orthodontic adhesives polymerizing chemically or with light. We also aimed to check whether a single rinse is effective on evacuating all the residual monomers. Methods: Light curing (Transbond XT, Unitek, CA, USA and Opal Seal Ultradent, Utah, USA) and chemically curing adhesives (Rely-a bond, Reliance Orthodontic Products, Inc., USA and Unite, 3M/Unitek, CA, USA) were used to bond upper and lower braces of 48 patients. Patients gargled 25 mL drinking water for 1 minute; before bonding (T0), immediately after bonding (T1) and immediately after the first rinse (T2). The samples were placed in amber colored glass bottles, preserved in -20 degrees C and filtered through a 0.45-micron filter and analyzed with Liquid Chromatography Tandem Mass Spectrometry. Results: Bis-GMA release was recorded with all the adhesives. Higher amount of residual monomer was recorded for the light curing composite adhesives; Transbond XT and Opal Seal, followed by chemically curing; Unite and Rely-a bond. There was no statistically significant difference in Bis-GMA concentration at T1 and T2 (p>0.05). Conclusion: Significant release of Bis-GMA was observed following orthodontic bonding with either light or chemically curing adhesives. No significant difference was recorded between the first and the second rinses following bonding, meaning that a single rinse may not be effective in evacuating all the residual monomers.
Keywords: Bis-GMA; orthodontic adhesives; liquid chromatography